Agility Analysis to Review Economic Resilience in Micro, Small and Medium Enterprises - Indah Putri; Fadli Agus Triansyah; Aulia Rachma Dinantika; Ashari Gunawan (Cita Konsultindo Research Center, 2023)
SME is one of the most influential factors to economic growth in Indonesia. This research is done because the number of SME are stagnant and almost close to bankruptcy. This will have an impact on economic resilience of SME. This study aims to investigate the effect of Knowledge Stikiness and Absorptive Capacity on SMEs Agility, and test the impact of SMEs agility on Economic Resilience. The data were collected through SME survey method throughout Medan, North Sumatera, Indonesia. With random sampling technique, researchers got 134 respondents. Furthermore, the data were analyzed by SEM-PLS. The results show that knowledge stickiness has a negative effect on SMEs agility. In addition, the Absorptive Capacity variable has a positive effect on SMEs agility. Furthermore, SME's agility has a positive effect on Economic Resilience. Finally, both the Absorptive Capacity and Stunt of SMEs have a significant and positive impact on Economic Resilience. This study recommends an increase in Absorptive Capacity of SMEs agility in Medan City. This increase will have a major impact on economic resilience and emphasize the economic progress of SMEs. In addition, stakeholders should take strategic action to improve the agility and economic resilience of SMEs.